Post transcriptional gene silencing in transgenic plants - Carvalho Balieiro, Fabiano de; Boerjan, Wout; Ingelbrecht, I.L.; Depicker, A.; Inze, D.; Montagu, M. van (1994)
The recent successes of gene engineering in plants demonstrate the high potential of expressing transgenes in agronomically important crops. These approaches require that the introduced gene is stably expressed in subsequent plant generations. However, experiments involving transgenic plants show that the expression of chimeric genes can substantially vary among individual transformants.